Effect of operating conditions and feedstock composition on the properties of manganese oxide or quartz charcoal pellets for the use in ferroalloy industries. (15th February 2020) - Surup, Gerrit Ralf; Nielsen, Henrik Kofoed; Großarth, Marius; Deike, Rüdiger; Van den Bulcke, Jan; Kibleur, Pierre; Müller, Michael; Ziegner, Mirko; Yazhenskikh, Elena; Beloshapkin, Sergey; Leahy, James J.; Trubetskaya, Anna
Abstract: This study investigates the effect of heat treatment temperature on the properties of charcoal composite pellets used for the reduction of ferroalloys. The heavy fraction of biooil was used as a binder for the charcoal ore pellet preparation. The effect of heat treatment temperature on the pellet shrinkage was related to the degree of reduction which varied with feedstock and ore composition. The results showed that the size and shape of the charcoal pellets were not affected by the biooil devolatilization. Manganese charcoal pellets showed higher electrical resistance during pyrolysis, whereas the structure, composition and electrical resistance of silica composite pellets remained unaffected by heat treatment temperatures < 1650 °C. However, the secondary heat treatment decreased the CO2 gasification reactivity and electrical resistivity of charcoal composite pellets. In addition, the findings of this work demonstrate the potential for using biooil as a binder for the charcoal composite pellets used in ferroalloy industries. The composite pellets are suitable to pre-reduce the manganese ore in the low temperature zones of an industrial furnace, and the charcoal pellets can be used as an alternative bed material. However, the high CO2 reactivity may create challenges during the direct replacement of metallurgical coke with the bio-reductants. Highlights: The charcoal composite pellets were heat treated at 1650 °C. Co-pyrolysis of charcoal with biooil increase the pellet porosity. The size, shape and inner porosity of SiO2 charcoal pellets changed only slightly. Composite pellets can pre-reduce the Mn ore in the low temperature zones of a furnace.